2013
DOI: 10.1159/000354346
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Processing in Infancy

Abstract: This chapter provides an overview of behavioral and neurophysiological research on the discrimination and categorization of emotional expressions in the first year of life. Three recent lines of research with theoretical implications beyond perceptual discrimination of facial expressions are discussed. The first focuses on the development of attentional biases towards facial expressions. Between 5 and 7 months of age infants start to attend preferentially towards fearful faces rather than happy faces and disen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 58 publications
(101 reference statements)
3
26
0
6
Order By: Relevance
“…The authors suggested that during the very first days of postnatal life newborns are mostly exposed to smiling faces with directed gaze and this facial expression is crucial to promote social interactions [ 9 ]. This is in line with evidence demonstrating that early in life infants are more attracted by smiling faces [ 11 ], and are facilitated in the recognition of face identity when faces display a happy emotional expression [ 12 , 13 ]. However, both of these studies [ 8 , 9 ] used as stimuli static photographs in which the perceptual differences between the two facial expressions were very pronounced.…”
Section: Introductionsupporting
confidence: 89%
“…The authors suggested that during the very first days of postnatal life newborns are mostly exposed to smiling faces with directed gaze and this facial expression is crucial to promote social interactions [ 9 ]. This is in line with evidence demonstrating that early in life infants are more attracted by smiling faces [ 11 ], and are facilitated in the recognition of face identity when faces display a happy emotional expression [ 12 , 13 ]. However, both of these studies [ 8 , 9 ] used as stimuli static photographs in which the perceptual differences between the two facial expressions were very pronounced.…”
Section: Introductionsupporting
confidence: 89%
“…Moreover, 5‐month‐old infants showed selective facial activity in response to bimodal, but not unimodal, laughing and crying emotional expressions (Isomura & Nakano, ). In sum, these EMG studies are in line with behavioural and neuroimaging evidence showing that emotional processing abilities undergo significant development in the first year of life (Grossmann, Striano, & Friederici, ; Hoehl, ). Second, these studies suggest that EMG is a valid technique to detect infants’ sensitivity to the valence of facial expressions.…”
Section: Introductionsupporting
confidence: 85%
“…By the end of the first year of life, infants possess sophisticated emotion perception skills: They can discriminate between different emotions from faces and bodies, categorize and recognize emotions and use emotional cues coming from their caregivers to guide their actions in their environment (Hoehl, ). Here, we have shown that, besides facial expressions and static body postures, infants can extract emotion‐related information also from action kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…This does not, however, preclude the possibility that faster attention to negative stimuli develops with age or is learned from experience. Preferential looking to fearful faces over happy or neutral expressions does not emerge until 7 months, coinciding with when infants first learn to crawl and parents start directing more negative affect toward them (see Hoehl, 2014; Leppänen, 2016). More frequent exposure to negative or hostile environments also increases perceptual sensitivity to anger (Cicchetti & Ng, 2014; Pollak & Tolley-Schell, 2003).…”
Section: Discussionmentioning
confidence: 99%